Association of the stress hyperglycemia ratio for all-cause and cardiovascular mortality in population with cardiovascular-kidney-metabolic syndrome stages 0–4: evidence from a large cohort study - Fan-Shun Guo; Jia-Hao Dou; Jun-Xiang Wang; Chen Guo; Rui-Yun Wu; Xue-Lu Sun; Yi-Wei Hu; Jin Wei (Diabetology & Metabolic Syndrome)
Abstract Background The Cardiovascular-kidney-metabolic (CKM) syndrome is a health disorder caused by interactions between cardiovascular disease, kidney disease, and metabolism-related risk factors. The stress hyperglycemia ratio (SHR) has been shown to correlate with the prognosis of participants with diabetes mellitus, heart failure, and myocardial infarction. However, the predictive value of SHR in the CKM syndrome population is unclear and requires further exploration. Methods This study analyzed 19,345 participants from the National Health and Nutrition Examination Survey (1999–2018). CKM syndrome was staged according to the American Heart Association (AHA) guidelines. SHR was calculated using fasting blood glucose (FBG) and glycated hemoglobin type A1c (HbA1c). Participants were grouped into four quartiles based on SHR. The primary and secondary outcomes were all-cause mortality and cardiovascular mortality, respectively. Kaplan-Meier survival curves and Cox proportional hazard regression models were used to evaluate the association between SHR and outcomes. Then, the potential nonlinear relationship was explored using restricted cubic spline (RCS) analysis. We also performed subgroup analyses to assess the effects of different variables. Results A total of 2,736 all-cause deaths and 699 cardiovascular deaths were recorded during a median follow-up period of 115 months. Kaplan-Meier analysis revealed that participants in quartile 2 had the lowest risk for both all-cause and cardiovascular mortality (Log Rank P < 0.05). Multivariate Cox regression demonstrated the lowest all-cause mortality in the 2nd quartile (HR = 0.84, 95% CI = 0.73–0.97, P = 0.015) and the highest all-cause mortality in the 4th quartile (HR = 1.19, 95% CI = 1.03–1.37, P = 0.018), compared with the 1st quartile group of SHR. The RCS curve demonstrated a U-shape association of SHR with both all-cause and cardiovascular mortality, with the lowest points of 0.89 and 0.91, respectively. Conclusions SHR is strongly correlated with prognosis in the CKM syndrome population, with high or low SHR increasing the risk of death. This index shows great potential for predicting the risk of death in this population.